Single and binary mixture toxicity of ibuprofen and paracetamol to Daphnia magna - Slogar, V. (2021)
Pharmaceuticals are a diverse group of compounds biologically active, produced to treat human and animal diseases. They enter the environment mainly in two ways, waste water effluent from human sources and agricultural runoff from veterinay treatments. As removal of a large number of pharmaceuticals from sewage treatment processes is not complete, mixtures of pharmaceuticals are discharged into the receiving waters in detectable amounts. The aim of this study was to assess the acute and chronic effects of paracetamol, ibuprofen and its mixture, at ecologically relevant concentrations in the freshwater crustacean Daphnia magna